Tuberculosis in Adolescents in Bulgaria for a Three-Year Period: 2018-2020 - Natalia Gabrovska; Albena Spasova; Anabela Galacheva; Dimitar Kostadinov; Nikolay Yanev; Vladimir Milanov; Kaloyan Gabrovski; Svetlana Velizarova (MDPI AG, 2022)
Background: Each year, approximately two million adolescents and young adults in the world become infected with tuberculosis (TB). The problem is that the classification of the disease includes children in the age group 0-14 years and young adults aged 15 and over. The present study aims to analyze and compare the epidemiology and clinical presentation of TB in Bulgaria in the different age subgroups of childhood. Methods: A retrospective study was undertaken of the newly diagnosed children (n = 80) with TB treated onsite from January 2018 to December 2020 at the Multiprofile Hospital for Active Treatment of Pulmonary Diseases ("St. Sofia"). They were distributed into three age groups: aged 8-11 (prepuberty), aged 12-14 (younger adolescents), and aged above 15 (older adolescents). Results: A clear finding of the research indicated that adolescent children develop TB both as primary and secondary infections. In a large number of cases with the children under our care, we found enlarged intrathoracic lymph nodes as well as infiltrative changes in the lungs, i.e., we observed transitional forms. There were statistically significant differences between the age group >15 years old and each of the other two younger groups for diagnosis, the severity of intoxication, and BK spreading status. Conclusion: The course of tuberculosis in adolescence has its own specifics and differences between the three age groups in the current study.